Critical Time Intervals in Door-to-Balloon Time Linked to One-Year Mortality in ST-Elevation Myocardial Infarction - Shin-Ho Tsai; Yu-Ting Hsiao; Ya-Ni Yeh; Jih-Chun Lin; Shi-Quan Zhang; Ming-Jen Tsai (Western Journal of Emergency Medicine)
Background: Timely activation of primary percutaneous coronary intervention (PCI) is crucial for patients with ST-segment elevation myocardial infarction (STEMI). Door-to-balloon (DTB) time, representing the duration from patient arrival to balloon inflation, is critical for prognosis. However, the specific time segment within the DTB that is most associated with long-term mortality remains unclear. In this study we aimed to identify the target time segment within the DTB that is most associated with one-year mortality in STEMI patients. Methods: We conducted a retrospective cohort study at a tertiary teaching hospital. All patients diagnosed with STEMI and activated for primary PCI from the emergency department were identified between January 2013–December 2021. Patient demographics, medical history, triage information, electrocardiogram, troponin-I levels, and coronary angiography reports were obtained. We divided the DTB time into door-to-electrocardiogram (ECG), ECG-to-cardiac catheterization laboratory (cath lab) activation, activation-to-cath lab arrival, and cath lab arrival-to-balloon time. We used Kaplan-Meier survival analysis and multivariable Cox proportional hazards models to determine the independent effects of these time intervals on the risk of one-year mortality. Results: A total of 732 STEMI patients were included. Kaplan-Meier analysis revealed that delayed door-to-ECG time (>10 min) and cath lab arrival-to-balloon time (>30 min) were associated with a higher risk of one-year mortality (log-rank test, P < .001 and P = 0.01, respectively). In the multivariable Cox models, door-to-ECG time was a significant predictor for one-year mortality, whether it was analyzed as a dichotomized (>10 min vs ≤10 min) or a continuous variable. The corresponding adjusted hazard ratios (aHR) were 2.81 (95% confidence interval [CI] 1.42–5.55) for the dichotomized analysis, and 1.03 (95% CI 1.00–1.06) per minute increase, respectively. Cath lab arrival-to-balloon time also showed an independent effect on one-year mortality when analyzed as a continuous variable, with an aHR of 1.02 (95% CI 1.00–1.04) per minute increase. However, ECG-to-cath lab activation and activation-to-cath lab arrival times did not show a significant association with the risk of one-year mortality. Conclusion: Within the door-to-balloon interval, the time from door-to-ECG completion is particularly crucial for one-year survival after STEMI, while cath lab arrival-to-balloon inflation may also be relevant.